Supporting self-care in general practice - Greaves, Colin J (Oxford University Press, 2007)
There is both a clear need and a political will to improve self-care in long-term conditions: demand for self-care support interventions is rising. This article discusses current approaches to supporting self-care in primary care, evidence in favour of self-care support, and issues for GPs to consider in planning self-care support systems. In planning care pathways, important choices need to be made about whether to use individual or group-based approaches and what intensity of intervention is appropriate to match patient needs. Investment may also be needed in both health professional competences and practice systems to optimise their ability to support patient self-care. Self-care support is a key approach for the future of UK health care. Practices that are well trained and well organised to support self-care will respond better to the complex challenges of achieving improvements in the outcomes of long-term conditions.